Analisis SWOT/TOWS Untuk Perencanaan Strategis Sistem Informasi dan Teknologi Informasi Pada SMK di Kota Lubuklinggau - Okto Kurnia (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2020)
Currently, information and communication technology (ICT) has become an important sector for administering education in schools. The use of Information and Communication Technology is one of the determining aspects in competition. The condition of ICT in Vocational High Schools (SMK) in Lubuklinggau City has not fully used ICT-based applications, several schools that already have ICT applications and infrastructure are built themselves and are managed according to local needs both in the administration section and the support units. Meanwhile, on the other hand, there are still aspects of the public that are not yet based on ICTs with inadequate ICT facilities / infrastructure to support the success of organizational goals in the field of education optimally. For this reason, the researcher wants to help the Education Office of the City of Lubuklinggau to plan a technology strategy and information system that can be used as a guide in the ICT strategic plan. This study uses the SWOT / TOWS matrix as one of the methods applied for internal analysis in order to produce strategic planning proposals for ICT development for vocational schools in Lubuklinggau City.